How to raise and educate a child with special educational needs - Martínez Ocaña, Bertha E. (2016)
When parents find out that their children have a disability The family is the most natural and necessary basic social community; in it must be given in a very special degree, all those fundamental values; This is communication, dialogue, self-determination, collaboration and love.